KEBERLANGSUNGAN BISNIS UMKM BERDASARKAN LITERASI KEUANGAN DIGITAL DAN RISIKO KEUANGAN DIGITAL DI DAERAH LAHAN BASAH KOTA BANJARMASIN - Jikrillah, Sufi; Juniar, Asrid (JWM (JURNAL WAWASAN MANAJEMEN), 2024)
The purpose of this research is to provide solutions and understanding regarding digital financial literacy as the sustainability of MSMEs in facing uncertain conditions, identifying digital financial risks, assessing potential digital financial risks that may arise, and analyzing the strategies that MSMEs will implement to address or manage these digital financial risks. In this study, a Census Sampling method is used, which is a sampling method where all members of the population are used as samples (Sugiyono, 2014). The number of the population and the sample is the same (saturated sample) from this study, which consists of MSME entrepreneurs in the Sasirangan village, Ketupat village, and Purun village. The number of samples used in this study is 30 SMEs. The results of this study indicate a positive and significant impact of digital financial literacy on the profit growth of SMEs. The most impactful financial risks that need immediate management/treatment are: Digital Market Risk and Digital Credit Risk, which often occur and have significant impacts, as well as Digital Liquidity Risk and Digital Capital Risk, which sometimes occur and have moderate impacts.